Kozeny-Carman constant of porous media: Insights from fractal-capillary imbibition theory. (15th December 2018) - Wei, Wei; Cai, Jianchao; Xiao, Junfeng; Meng, Qingbang; Xiao, Boqi; Han, Qi
Abstract: The Kozeny-Carman (KC) equation has been widely used in many fields including shale and tight reservoirs, soil physics and chemical engineering. However, accurate calculation of KC constant is always a challenge. This work focuses on analysis of the KC constant in capillary imbibition process based on fractal distribution characteristics of hydraulic pore diameter. The proposed model incorporates gravity over the entire time frame of imbibition process, which is expressed in terms of porosity, fractal dimension, tortuosity, maximum hydraulic pore diameter, liquid density, viscosity, surface tension and contact angle. The theoretical predictions from the developed model provide a good agreement with experimental results of emulsion imbibition, with values of fractal dimension and tortuosity from fitting of height-time data of emulsion imbibition.